2020
DOI: 10.1186/s12879-020-05698-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbidol (Umifenovir) on COVID-19: a randomized controlled trial

Abstract: Background Treatment of patients with COVID-19 has included supportive care to mainly relief symptoms of the disease. Although World Health Organization (WHO) has not recommended any effective treatments for COVID-19, there are some reports about use of antiviral drugs. The aim of this study is to determine the effect of Arbidol (ARB) on COVID-19 disease. Methods Using an open-label randomized controlled trial, we examined the efficacy of ARB in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 24 publications
2
135
0
3
Order By: Relevance
“…One single trial randomizing 78 participants compared bromhexine hydrochloride versus standard care and showed evidence of a beneficial effect of bromhexine hydrochloride on admittance to intensive care ( p = 0.013) and receipt of mechanical ventilation ( p = 0.014) [ 103 ]. One single trial randomizing 100 participants compared hydroxychloroquine combined with arbidol versus hydroxychloroquine combined with lopinavir-ritonavir and showed evidence of a beneficial effect of hydroxychloroquine combined with arbidol on admission to intensive care ( p = 0.0001) [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…One single trial randomizing 78 participants compared bromhexine hydrochloride versus standard care and showed evidence of a beneficial effect of bromhexine hydrochloride on admittance to intensive care ( p = 0.013) and receipt of mechanical ventilation ( p = 0.014) [ 103 ]. One single trial randomizing 100 participants compared hydroxychloroquine combined with arbidol versus hydroxychloroquine combined with lopinavir-ritonavir and showed evidence of a beneficial effect of hydroxychloroquine combined with arbidol on admission to intensive care ( p = 0.0001) [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…However in another study, umifenovir was shown to shorten the viral shedding interval as well as decreased the duration and cost of hospitalization for non-severe, COVID-19 patients ( Wang et al, 2020d ). A randomized controlled trial from Iran also highlighted that umifenovir monotherapy significantly contributes to clinical and laboratory improvements in COVID-19 patients including peripheral oxygen saturation, ICU admissions, hospitalization duration, ESR, WBC, and chest CT requirements ( Nojomi et al, 2020 ). A randomized, double-blinded, placebo-controlled, Phase III trial is ongoing in India for the use of umifenovir to analyze the efficacy, safety, and tolerability of umifenovir in Indian COVID-19 patients (CSIR, 2020) ( Kitagawa et al, 2020 ).…”
Section: Covid-19 Therapeuticsmentioning
confidence: 99%
“…55, 58, 68, 81, 93, 101, 122, 123 Treatments in four trials were not connected in the network. 73, 77, 86, 98…”
Section: Resultsmentioning
confidence: 99%